The Narrative Architecture of Commerce: A Structural Model of Storytelling-Induced Engagement and Purchase Intention in the Digital Age - Ms. Nirali R. Shah; Dr. Jaygiri Goswami (Journal of Advanced Research in Operational and Marketing Management, 2026)
The digital marketing landscape of 2025 is defined by an overwhelming saturation of information, where traditional promotional strategies encounter cognitive resistance. This research investigates "Storytelling as a Strategic Marketing Tool", proposing a structural model that delineates the pathways from narrative exposure to purchase intention. It prioritises a qualitative-dominant mixed-methods design, utilising narrative transportation theory to explore the "why" behind consumer behaviour. The research follows a purposive sampling approach aimed at meaning saturation, validated by Partial Least Squares Structural Equation Modelling (PLS-SEM) to confirm behavioural paths. Findings indicate that character-driven narratives and "story-doing" significantly bypass scepticism by establishing emotional resonance and radical authenticity. The data analysis integrates thematic clusters with inter-rater reliability checks and model fit indices that exceed standard thresholds. Results demonstrate that perceived authenticity is the strongest predictor of intention. The study concludes that strategic marketing in 2026 must transition toward generative, personalised media and purpose-driven experiences to foster long-term loyalty.